O cosmopolitismo kantiano : do melhoramento dos costumes humanos à instituição da paz - Zanella, Diego Carlos (2012)
The aim of this thesis is to defend Kantian cosmopolitanism as a proposal to progressively and continuously organize the political and legal relations in the world. This proposal has, on the one hand, clearly Stoic roots. On the other hand, it shows the Enlightenment ideals of Kant s time as intrinsic to cosmopolitanism. Due to this, this proposal does not sufficiently separate the spheres of law and morality, which end up being the essential parts of Kantian cosmopolitanism. The moral sphere puts forward the idea that every rational being should think and act as a world citizen, so as to respect others. The political sphere puts forward the idea that global citizenship requires an international organization that administers the cosmopolitan law. In this sense, each of these spheres has a particular area of expertise: the moral domain manifests itself in people s relations with each other, while the political field is manifested in the structure of political and legal institutions and their relationships, whether between institutions themselves or between institutions and citizens. Moreover, this consideration also has to go through the understanding of human destiny, that is, by the understanding that the human beings are determined to live in society and improve themselves in it, as well as its institutions.